Modelling the Dynamic Impact of Fertilizer Subsidy on Paddy Production: Empirical Evidence from Sri Lanka - Ginige, Senaka Ramyanath; Cooray, N.S. (Journal of Reviews on Global Economics, 2020)
Rice is the main staple food in Sri Lanka. There will be a potential increase in demand for rice due to the high population growth in the years to come. As the cultivable area is limited, the only way to increase required supply is to improve the yield level. However, there are a limited number of district level studies, which examined the factors that influence the paddy production in Sri Lanka. Hence, this study aims to identify the factors, which increase the paddy production in Sri Lanka with particular reference to fertilizer usage, guaranteed paddy price, temperature and rainfall. District-wise data were collected over the period from 1979 to 2019. An autoregressive distributed lag (ARDL) model was used to examine the short-run and long-run relationships between the paddy production and explanatory variables. According to the estimated model, the temperature has both significant positive and negative long-run relationships with paddy production in several districts. Furthermore, results reveal that paddy production in many districts had positive long-run relationships with the usage of the mixture of organic and chemical fertilizer. Hence, the findings of this study provide valuable policy insight for decision makers to redesign the chemical fertilizer subsidy in Sri Lanka. Our results also reveal that the use of organic fertilizer contributes to an increase in paddy production in both short-run and long-run. Hence, it is our opinion that sustainable agricultural practices combined with the removal of market distortions will lead to establishing an economically efficient paddy production system in Sri Lanka.